Unravelling genomic drivers of speciation in Musa through genome assemblies of wild banana ancestors - Guillaume Martin; Benjamin Istace; Franc-Christophe Baurens; Caroline Belser; Catherine Hervouet; Karine Labadie; Corinne Cruaud; Benjamin Noel; Chantal Guiougou; Frederic Salmon; Joël Mahadeo; Fajarudin Ahmad; et al. (Nature Communications)
Abstract Hybridization between wild Musa species and subspecies from Southeast Asia is at the origin of cultivated bananas. The genomes of these cultivars are complex mosaics involving nine genetic groups, including two previously unknown contributors. This study provides continuous genome assemblies for six wild genetic groups, one of which represents one of the unknown ancestor, identified as M. acuminata ssp. halabanensis. The second unknown ancestor partially present in a seventh assembly appears related to M. a. ssp. zebrina. These assemblies provide key resources for banana genetics and for improving cultivar assemblies, including that of the emblematic triploid Cavendish. Comparative and phylogenetic analyses reveal an ongoing speciation process within Musa, characterised by large chromosome rearrangements and centromere differentiation through the integration of different types of repeated sequences, including rDNA tandem repeats. This speciation process may have been favoured by reproductive isolation related to the particular context of climate and land connectivity fluctuations in the Southeast Asian region.